2019
DOI: 10.1055/a-0735-9107
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of EUS-FNA in patients receiving antithrombotic therapy

Abstract: Background and study aims  To investigate bleeding risk and thromboembolic risk in patients receiving antithrombotic therapy who underwent endoscopic ultrasound-guided fine-needls aspiration (EUS-FNA). Patients and methods  A single-center retrospective study of 908 consecutive patients undergoing EUS-FNA for pancreatic and non-pancreatic lesions patients between March 2013 and March 2017 was performed. Antithrombotic management was classified into three groups: continuous, discontinuation, and heparin replac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 17 publications
0
13
1
Order By: Relevance
“…7 This finding was consistent with those of other single-center studies. 6,8 In the present study, the number of patients in the ATA group (especially in the anticoagulant group) was small. Therefore, we could not make a judgment about the differences among the antithrombotic drugs.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…7 This finding was consistent with those of other single-center studies. 6,8 In the present study, the number of patients in the ATA group (especially in the anticoagulant group) was small. Therefore, we could not make a judgment about the differences among the antithrombotic drugs.…”
Section: Discussionmentioning
confidence: 63%
“…4 Two previous studies from Japan on EUS-FNA in patients with antithrombotic therapy found a low incidence of EUS-FNA-related bleeding in patients receiving antithrombotic therapy (0.4%-1.0%). 6,8 The bleeding event rate was low even in patients who underwent EUS-FNA while continuing antithrombotic therapy. The bleeding risk was found to increase according to the type of antithrombotic drugs (e.g., warfarin and heparin).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conclusion of the study was that EUS-FNA was a safe procedure for patients using antithrombotic agents, even when antithrombotic therapy is not discontinued during EUS-FNA. [ 52 ] A retrospective study conducted with 742 consecutive patients who underwent EUS-FNA for solid lesions compared bleeding event rates among patients not using antithrombotic agents, those discontinuing their use, those continuing treatment with aspirin or cilostazol, and those who were on replacement therapy with heparin. A low incidence of EUS-FNA-related bleeding in patients receiving antithrombotic treatment was found; the bleeding event rate was low even in patients who underwent EUS-FNA while continuing aspirin or cilostazol.…”
Section: Discussionmentioning
confidence: 99%
“…The only significant differences were between patients on prophylactic low molecular weight heparin and controls [128]. In the largest study, however, no severe haemorrhage was found in patients who continued or discontinued antithrombotic therapy, and only one thromboembolic event occurred [129].…”
Section: Endoscopic Ultrasound-guided With Fine-needle Aspiration (Eus-fna) and Other Interventionsmentioning
confidence: 99%